APKASS consensus statement on chronic syndesmosis injury - Yujie Song; Zhongmin Shi; Hiroaki Kurokawa; Yasuhito Tanaka; Samuel Ka-Kin Ling; Patrick Shu-Hang Yung; Chayanin Angthong; Seung Hwan Han; Yinghui Hua; Hongyun Li; Chen Jiao; Jianchao Gui; et al. (My University, 2021)
Experts from the Asia-Pacific Knee, Arthroscopy and Sports Medicine Society (APKASS) convened to develop expert-and evidence-based consensus statements in order to assist surgeons and physical therapists in the management of chronic syndesmosis injury.The purpose of this article was to report the results that took place at the 2020 APKASS international consensus meeting on this challenging disorder. MethodsA core group of 13 authors drafted and refined 13 items consisting of 38 clinical questions and statements, which were then assigned to at least 1 of the authors to research and summarize the currently available evidence.Our consensus methodology was designed using a 2-stage Delphi process, which included an online survey (November 20, 2020; stage 1) and an online meeting (December 20, 2020; stage 2).The final document we sent out for stage 1 of the consensus process featured 8 items and 29 statements (available as supplemental material).Each statement was
Keywords: Syndesmosis; Statement (logic); Consensus conference; Interstitial Lung Diseases and Idiopathic Pulmonary Fibrosis